Geospatial analysis of land degradation and settlement in Barru Regency: Implications for sustainable land management - Amiruddin, Hamman Badruttamanan; Arif, Samsu; Sakka, Sakka (Brawijaya University, 2026)
Residential zones are designated for housing and activities that support livelihoods. In Barru Regency, South Sulawesi, Indonesia, a growing population has increased the demand for residential land, intensifying land degradation issues such as landslides in Bulobulo Village, erosion in the Lisu Watershed, and mangrove loss on Pannikiang Island, which is fueled by unsustainable land use and mining practices. This study examined the relationship between population size and optimal settlement land, while assessing the compatibility of suitable land with the Barru Regency Spatial Plan (RTRW) for the period 2011-2031. The methodology employed geospatial analysis using GIS overlay techniques and mathematical modeling, incorporating flood and landslide vulnerability to evaluate carrying capacity. Results revealed that all sub-districts had a carrying capacity index (DDPm) above 1, but only 1,563.2 ha of the 33,694.2 ha identified as suitable overlapped with RTRW allocations, exposing a critical mismatch. This mismatch indicates that current spatial planning does not adequately integrate land degradation risks. The findings provide evidence-based guidance for revising the RTRW, supported by practical restoration strategies, including reforestation of degraded watersheds, slope stabilization in landslide-prone areas, and community-based mangrove rehabilitation. By linking geospatial mapping with management recommendations, this study contributes a novel framework for sustainable and disaster-resilient settlement planning on degraded lands.